'Active, young, and resourceful': sorting the 'good' tenant through mechanisms of conditionality. Issue 8 (22nd October 2021) - Costarelli, Igor; Kleinhans, Reinout; Mugnano, Silvia
Abstract: Governments' attempts to link the provision of welfare services to (more) responsible self-conduct of citizens (i.e. responsibilization) is seen as a distinctive feature of the post-welfare state. Responsibilization often requires welfare receivers to comply with specific duties or behavioural patterns (i.e. conditionality). Except for UK-based studies, little is known about responsibilization strategies of social housing tenants based on specific allocation policies or management approaches. To fill this gap, this paper examines recent cases of tenants' responsibilization through conditionality, i.e. allocation of housing on the condition that receivers regularly engage in supportive activities, in Utrecht (The Netherlands) and Milan (Italy). Through a qualitative methodology, this paper unpacks the use of conditionality as a means to increase tenants' responsibilization. The paper contributes by showing both innovative aspects, such as eligibility criteria, obligations, accountability measures, and potential pitfalls connected to diverging expectations between tenants and professionals, and to specific context-related factors.